Association between IL-1β + 3954C/T polymorphism and myocardial infarction risk: A meta-analysis. Issue 30 (July 2018) - Fang, Yizhen; Xie, Huabin; Lin, Zhiyuan
Abstract: Background: Many studies have reported that the IL-1β + 3954C/T polymorphism (rs1143634) is related to myocardial infarction (MI). To classify the association between IL-1β + 3954C/T and MI susceptibility, we performed a meta-analysis. Methods: We retrieved relevant literature from electronic databases (Embase, PubMed, Cochrane, and Web of Science). Pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated with a fixed effect model or a random effect model. Sensitivity analysis and publication bias results are also presented. Results: Nine eligible studies (2299 controls and 2203 cases) were included. The pooled results showed a significant relationship between MI and IL-1β + 3954C/T in an allelic comparison (T vs C: OR = 1.13, 95% CI 1.02–1.25, I 2 = 0%, P H = .448) and in a dominant model (TC + TT vs CC: OR = 1.15, 95% CI 1.02–1.30, I 2 = 0%, P H = .880). Ethnic subgroup analysis showed similar results in Caucasian populations: an allelic comparison (T vs C: OR = 1.16, 95% CI 1.04–1.29, I 2 = 0%, P H = .701), homozygote model (TT vs CC: OR = 1.36, 95% CI 1.04–1.79, I 2 = 0%, P H = .673), and dominant model (TC + TT vs CC: OR = 1.17, 95% CI 1.02–1.33, I 2 = 0%, P H = .851). In addition, similar effects remained in subgroups analyses of high-quality studies and PCR-RFLP (restriction fragment length polymorphism) data. Conclusion: Our meta-analysis proved that IL-1β + 3954C/T is associated with MI susceptibility, especially among Caucasian populations.